(Bio)porodi rekk ? Structuration des savoirs paysans de protection des cultures et dépendance aux pesticides en maraîchage – Cas d’une commune maraîchère de la zone des Niayes (Sénégal) - Baptiste Gaillard (VertigO)
In Senegal, the use of pesticides in vegetable production is a widespread and persistent practice. This situation is apparent from the synthetic formula 'porodi rekk' ('just pesticides' in Wolof), by which vegetable producers usually summarise their approach to pest management. The aim of this paper is to explore the knowledge of vegetable producers regarding crop protection, and to analyse the contribution of such knowledge to the reproduction of chemical pest control in the Senegalese vegetable sector. To this end, this paper analyses how this knowledge is structured by the material and social network with which it is associated, and how this knowledge in turn structures the practices of vegetable producers. The chosen method consisted in a case study centred on a (anonymised) commune in the Niayes area – the main vegetable production basin in Senegal. Forty-eight (48) semi-structured interviews were conducted with vegetable producers and pesticide dealers, before being analysed by inductive coding. The results show that the knowledge of vegetable producers is structured doubly i) by informal exchanges of advice between actors and ii) by an empirical-sensory understanding of pesticides and their effectiveness. This mode of structuration ensures the continued and incremental production of crop protection knowledge that includes i) a peasant classification of pesticides, ii) a dominant representation of the causes of phytosanitary problems, iii) an evolving knowledge of the most effective chemical treatments – but also iv) a large ignorance of the risks caused by chemical control on health and the environment. Finally, the current innovation process in vegetable crop protection – and the material and social network that underpins it – ensures the continuous improvement and reproduction of chemical control. Paradoxically, the promotion of biopesticides by certain development organisations and projects is aggravating the invisibilisation of the rare peasant' alternative knowledge. Beyond the role of knowledge, the literature suggests that the persistence of chemical control in the Senegalese vegetable sector is more broadly the result of a threefold political-institutional, technical-economic, and socio-cognitive lock-in.